Decoding Consumer Trust through the Lens of Micro-Influencer Authenticity in Emerging Markets - Enggal Sriwardiningsih; Erric Wijaya; Firdaus Putra (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid growth of social media in emerging markets has elevated the role of micro-influencers in shaping consumer behavior. This study investigates how micro-influencer authenticity (openness, consistency, emotional proximity) affects consumer trust and, in turn, purchase intention. A quantitative survey was administered to 85 respondents aged 18–35 who actively follow micro-influencers on Instagram and TikTok. Data were analyzed using validity and reliability tests, multiple regression, and mediation analysis (PROCESS Model 4) in SPSS. Results show that authenticity dimensions jointly explain 62% of variance in consumer trust (R² = 0.62), with openness (β = 0.41, p < 0.001), consistency (β = 0.33, p = 0.001), and proximity (β = 0.29, p = 0.002) all significant predictors. Consumer trust significantly predicts purchase intention (β = 0.56, p < 0.001), and mediates the effect of authenticity on purchase intention (indirect effect = 0.35, 95% CI [0.19, 0.50]). The findings indicate that authenticity functions primarily as a trust-builder, and trust serves as the key mechanism translating authenticity into purchase intent. Practical implications for marketers and influencer selection strategies are discussed.